Pengaruh Brand Image Terhadap Keputusan Nasabah Bank Kalbar Dalam Memilih Produk Tabungan Simpeda - Firman A (JURNAL MANAJEMEN MOTIVASI, 2014)
The research objective was to examine the influence of brand image on the customer's decision to choose products Savings Bank of West Kalimantan Simpeda. This type of research is descriptive. All customers who have the Savings Bank of West Kalimantan Simpeda the population, while the sample is 100 respondents who have Simpeda Savings Bank of West Kalimantan using incidental sampling technique. Analysis of the data used is simple linear. This research data obtained through observation, interviews and the results of a questionnaire distributed to respondents. The study's findingsindicate that the test results of multiple linear regression, it is known that the variable image producers and image of the products have a significant impact on customer decisions in choosing products Simpeda Savings Bank of West Kalimantan, while for consumer image variable has no effect, while the most influential variable is a variable the image of the product. From the test results simultaneously (F test) andpartial (test T) turns research results prove that all dimensions (image producers, consumers imagery and imagery products) of a brand image variables simultaneously have significant influence on customers' decisions in choosing Savings Simpeda, whereas in partial image of the consumer does not have a significant influence on brand image for variables that most influence on customers' decisions in choosing a savings product Simpeda is the image of the product.